Dissociation between function and manipulation in semantic representations of motor impaired subjects: A new test. Issue 3 (19th May 2022) - Graneri, Jorge; Dansilio, Sergio; Martínez-Cuitiño, Macarena; Grasso, Lina; Cantore, María Soledad; Brasca, Luciana
ABSTRACT: A fundamental problem in semantic cognition is the representation of human concepts in the brain. Much of the knowledge acquired in the last decades comes from the study of dissociations found in patients with acquired difficulties in language, perception, and action. In particular, some deficits involve loss of knowledge about tools. The dissociation between two relevant aspects of tools, function and manipulation, has been the focus of several studies. In this paper, a new test designed to study the dissociation between function and manipulation is proposed and normative values for a control population are provided. This novel test was additionally administered to and evaluated in a group of Parkinson's disease patients. The Graded-Controlled Hub-and-Spoke model of Lambon Ralph, Jefferies, Patterson and Rogers was used as a theoretical guide to interpret the results.